2018
DOI: 10.1007/978-3-319-78078-8_7
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review on Sleep Scheduling Mechanism in Wireless Sensor Networks

Abstract: Sleep scheduling, also known as duty cycling, which turns sensor nodes on and off in the necessary time, is a common train of thought to save energy. Sleep scheduling has become a significant mechanism to prolong the lifetime of WSNs and many related methods have been proposed in recent years, which have diverse emphases and application areas. This paper classifies those methods in different taxonomies and provides a deep insight into them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Since the amount of scavenged energy is so low (as Table 1 shows), in most cases the energy harvesting IoT device must operate on amounts of power as low as possible. Several strategies have been proposed for prolonging the lifetime of wireless IoT devices, including duty-cycling [104], sleep scheduling [105], the reduction of the required transmission distance for IoT devices through efficient clustering [106], optimized strategies for adaptively setting the rates of sensor reading and data transmission depending on available energy [107], or the development of scheduling schemes that take into account power consumption when waking up the wireless sensing systems [108]. Some practical techniques for reducing the energy required by an IoT device, also used in the development of low-power embedded systems, include Dynamic Voltage Scaling (DVS) [109], the reduction of the frequency of the processing unit [110], or the appropriate selection of peripherals in the device [111] or of the type of memory involved in data processing and storage (i.e., Flash or RAM -Random access memory) [112], the adaptation of transmission power depending on required communication range and environment [113,114], or logic for deciding the moment and format for sending slow varying data [115 -117].…”
Section: Energy Harvesting Modelingmentioning
confidence: 99%
“…Since the amount of scavenged energy is so low (as Table 1 shows), in most cases the energy harvesting IoT device must operate on amounts of power as low as possible. Several strategies have been proposed for prolonging the lifetime of wireless IoT devices, including duty-cycling [104], sleep scheduling [105], the reduction of the required transmission distance for IoT devices through efficient clustering [106], optimized strategies for adaptively setting the rates of sensor reading and data transmission depending on available energy [107], or the development of scheduling schemes that take into account power consumption when waking up the wireless sensing systems [108]. Some practical techniques for reducing the energy required by an IoT device, also used in the development of low-power embedded systems, include Dynamic Voltage Scaling (DVS) [109], the reduction of the frequency of the processing unit [110], or the appropriate selection of peripherals in the device [111] or of the type of memory involved in data processing and storage (i.e., Flash or RAM -Random access memory) [112], the adaptation of transmission power depending on required communication range and environment [113,114], or logic for deciding the moment and format for sending slow varying data [115 -117].…”
Section: Energy Harvesting Modelingmentioning
confidence: 99%
“…Further, duty cycling [78], i.e., scheduling the power on/off states of a RAT for radio communication, can be employed for additional security and improved longevity in devices capable of wireless communication. The ability to toggle the state of the RAT aligns well with concepts such as Collaborative Machine Learning (discussed further in Section 4.2.1), which focuses on improving a global model as a collective.…”
Section: Privacymentioning
confidence: 99%
“…The few survey study of sleep scheduling mechanism is summarized in the study of Zhang et al [42] and observed that most of the studies focused on asynchronous scheduling mechanisms. Moreover, the machine learning approach is widely applied in this field.…”
Section: Related Workmentioning
confidence: 99%